CVD-Diamant als Schutzschicht im Aluminiumguss - Helmreich, Thomas; Göltz, Maximilian; Mengele, Thomas; Rosiwal, Stefan (Gießerei-Praxis, 2020)
If aluminium melt comes into direct contact with a steel mould, the strong tendency of aluminium to react with iron (and other metals) leads to alloying of melt into the surface of the tool. This reduces the dimensional accuracy of the moulds and the demoulding as well as the working life of the mould. Therefore, time-consuming countermeasures such as spray treatments to improve the demolding or geometric restrictions are currently technically and economically necessary. Crystalline diamond layers applied by chemical vapour deposition (CVD) prevent direct contact between aluminium melt and steel tool. At common casting temperatures crystalline diamond exhibits no reaction with the aluminiu
Keywords: die casting; mould material; CVD-diamond layer; chemical vapour deposition; mould abrasion